Matru-Ke Revisited: CCA2-Secure Key Establishment Protocol Based on Matru - Akleylek, S.; Çevi̇k, N. (John Wiley and Sons Ltd vgorayska@wiley.com Southern Gate Chichester, West Sussex PO19 8SQ, 2020)
Quantum attack–resistant cryptosystems are required for secure communication since there is a big demand to have quantum computers. Lattice-based cryptography is one of the quantum-secure families due to its key/ciphertext sizes and performance. NTRU-based cryptosystems, a member of lattice-based cryptosystems, have received much more attention. MaTRU, a noncommutative version of NTRU with some matrix properties, is used to obtain a key exchange protocol in 2018. In this paper, we focus on MaTRU-based key exchange protocols having CCA2 properties. We propose CCA2-secure versions of MaTRU-KE and then provide a security analysis of CCA2-secure key establishment protocols. We also provide a comparison with the previous ones. © 2020 John Wiley & Sons, Ltd.
Keywords: CCA-CPA Security; Cryptography; Key Exchange; MATRU-KE; NTRU-Based Cryptosystems